Possible Relationship between Kalām and the Kalama Sutta - Peoples, Dion (The Journal of International Association of Buddhist Universities (JIABU), 2013)
Many people within the realm of Buddhist Studies are familiar with the Kalama Sutta and its functionality [also known by the alternative title: the Kesaputta Sutta], found in the Anguttara-Nikaya. Many people in Buddhist Studies do not know that this discourse is not isolated teaching given to the people of a village – it is replicated in other locations, and is given to a small group of monks and a householder. Kalam is familiar to anyone studying Islamic philosophy. KalƘm and the Kalama Sutta? Are the similarities too obvious or just some mere coincidental spelling? This article will explore this situation freely, from different perspectives.